The manner and time course of updating quantifier scope representations in discourse - Dotlačil, Jakub; Brasoveanu, Adrian (Language, cognition and neuroscience, 2015)
We present the results of two experiments, an eye-tracking study and a follow-up self-paced reading study, investigating the interpretation of quantifier scope in sentences with three quantifiers: two indefinites in subject and object positions and a universal distributive quantifier in adjunct position. In addition to the fact that such three-way scope interactions have not been experimentally investigated before, they enable us to distinguish between different theories of quantifier scope interpretation in ways that are not possible when only simpler, two-way interactions are considered. The experiments show that contrary to underspecification theories of scope, a totally ordered scope-hierarchy representation is maintained and modified across sentences and this scope representation cannot be reduced to the truth-conditional/mental model representation of sentential meaning. The experiments also show that the processor uses scope-disambiguating information as early as possible to (re)analyze scope representation.